Magnetic and Very Low Frequency Electromagnetic (VLF-EM) investigations for gold exploration around Ihale in Bunnu-Kabba Area of Kogi, north-central Nigeria - OSINOWO, Olawale Olakunle; FALUFOSI, Michael Oluseyi (Contributions to Geophysics and Geodesy, 2018)
This study integrates ground magnetic and Very Low Frequency Electromagnetic (VLF-EM) methods of geophysical investigation to probe the subsurface in terms of rock magnetic susceptibility and ground conductivity for the purpose of identifying mineralized pegmatite veins that could serve as host for gold and associated metallic deposits. Twenty five (25) carefully planned ground magnetic and VLF-EM profiles, each, were occupied east and west of a reference profile which was purposively established on an identified mineralized pegmatite vein around Ihale in Bunnu-Kabba area of Kogi, northcentral Nigeria. The acquired ground magnetic data were filtered and Reduced To Pole at Low Latitude (RTPLL) to remove regional field effect, cultural noise as well as focus the peaks of magnetic anomalies over corresponding sources. The measured raw real and raw imaginary components of the EM fields were subjected to Fraser and Karous Hjelt filtering to remove harmonic noise, focus and make anomaly amplitudes relate directly to the causative conductor as well as generate current density employed to characterise the subsurface. Seven (7) zones of relatively high VLF-EM derived current density with matching high residual positive magnetic anomalies present closely correlate-able signatures with subsurface response obtained around the reference profile established where local mining activities indicate evidence of gold and associated metallic mineralization of the pegmatite vein. The delineated zones constitute targets for gold and associated base metal prospects which could be further developed for economic benefit of the community.